Innovative practices of the university professor in virtual education during the COVID-19 pandemic - Meneses Claudio, Brian (2023)
This scientific research article analyzes the innovative practices of university teachers within the context of virtual education during the COVID-19 pandemic, applying a bibliographic review of various authors, considering that there are several innovative practices applied at the higher educational level, all based on virtual environments. The objective of the research work is to carry out an analysis of the innovative practices of university teachers in virtual education, in various databases such as SCOPUS, Web of Science (WoS), Dialnet, Scielo, E-Libro, Google Scholar, Gale Ebooks, Springer Link, IntechOpen, etc., considering the main ideas of the authors, their contributions, methodology, results, conclusions and recommendations. It is concluded that there is a direct relationship between the innovative practices of the university teacher and virtual education during the COVID-19 pandemic because a teacher trained with digital, methodological, and playful skills will be able to apply them in the teaching process, thus improving the student learning and generating the required competencies.